ANALYSIS OF OPPORTUNITIES AND CHALLENGES IN IMPLEMENTING CARBON TAX POLICY IN INDONESIA WITHIN THE TRIPLE BOTTOM LINE FRAMEWORK - udin , Bahrul Ulum; Leniwati, Driana; Jati, Ahmad Waluya; syam, Dhaniel; Wahyuni, Endang Dwi; Haryanti, Agustin Dwi (Kajian Akuntansi, 2024)
This research aims to analyze the opportunities and challenges in implementing carbon tax policies and assess public acceptance of these policies. It uses a descriptive qualitative approach, conducting interviews with five informants, including tax officials, tax academics/practitioners, company representatives, and the general public, from February to March 2024. The findings indicate that implementing carbon tax policies could increase government tax revenue, shift societal and business behavior toward lower carbon emissions, promote the transition to eco-friendly energy and technologies, and potentially reduce carbon emissions. However, challenges include rising prices of goods and services, decreased.   Keywords     : Carbon Tax Policy, Challenges, Opportunities